PHENOTYPIC DETECTION OF PLASMID FROM CIPROFLOXACIN RESISTANT SALMONELLA TYPHI ISOLATED FROM STOOL OF NSUK STUDENTS (FULafia Journal of Science and Technology, 2024)
Salmonella typhi (S. typhi) is a common cause of morbidity and mortality in developing countries. Studies onphenotypic detection of plasmid from ciprofloxacin resistant S. typhi isolated from stool of new students NasarawaState University, Keffi, was carried out. A total of 180 stool samples were collected from the new students. 30 stoolsamples were collected from each of the six respective Faculties. 29(16.1%) Salmonella isolates were recovered andidentified by standard Microbiological methods. 21(72.4%) of the isolates were Salmonella typhi and 8(27.6%)were Salmonella enteritidis. The prevalence of Salmonella typhi isolation with respect to Faculties was highest inthe Faculties of Art (ART) and Law (LAW) with 6(28.6%) isolates each. On the basis of gender, 15 samples eachwere collected from both male and female students respectively and the highest prevalence of isolation was 4(8.0%)amongst males in the Faculty of LAW and females in the Faculty of ART, while the least prevalence of isolationwas zero (0) amongst males in the Faculty of NAT. On the bases of age, the prevalence of isolation was highestamongst the age group 21-30, 19(10.5%), while age group 51-60 showed zero (0) prevalence of isolation.Antimicrobial Susceptibility was carried out using CLSI method; and 21(72.4%) Salmonella typhi isolates weresusceptible to Ciprofloxacin, while 8(27.6%) were resistant and the antimicrobial resistance phenotypic pattern ofthe isolates was also determined. The ciprofloxacin resistance isolates were subjected to “Curing Method” todetermine if the resistance was plasmid-mediated or not.